Formação em Economia Solidária e Educação Popular: aproximações e desafios - Poli, Odilon Luiz (2024)
Solidary Economy (Ecosol) and Popular Education, in junction, strengthen each other. The study approaches the importance of Popular Education in the consolidation of Economic and Solidary Enterprises (EES). It has had as its locustwo EES from Chapecó (SC). Data generated from the life stories of EES members and interviews with popular educators suggest that popular education practices were fundamental for the viability of the enterprises. Besides, these have promoted advances in the conditions of the subjects’ lives. However, these educational processes did not occur without contradictions and difficulties, including the resistance to participate, which might be a factor of fragility of the experiences concerning their continuity, in the perspective of Ecosol. Keywords: popular education, solidary economy, economic, solidary enterprises (EES).